Determinants of Affecting Factors Mortality of in The Elderly Covid-19 Patients - Sudarmi Sudarmi; Rohani Rohani; Irianto Irianto; Ni Putu Dian Ayu Anggraeni (Jurnal Kesehatan Prima, 2022)
The elderly groups to be infected with COVID-19 with a relatively high mortality rate, so they need attention. This study aims to determine the determinants of factors that affect the mortality of COVID-19 patients in the elderly in West Nusa Tenggara Province. The design of this study was cross-sectional with a purposive sampling technique, namely all elderly patients diagnosed with COVID-19 with PCR swab (+) who were treated in hospitals throughout NTB Province during the period March to December 2020. the total sample is 569 people. The variables of this study were age, gender, cluster, treatment status and, history of comorbidities. Data were analyzed using bivariate analysis using Chi-Square and multivariate with Logistic Regression. The results of the study were that most of the elderly COVID-19 patients were in the early 60-70 years (81.7%), the sex was primarily male 339 people (59.6%), without cluster 484 people (85.5%), history of comorbidities with comorbid 470 people (82.6%) and recovered after treatment 454 people (79.8%). COVID-19 patients in the elderly mainly died aged 60-70 years 85 people (73.9%), male sex, namely 71 people (61.7%), without cluster 107 people (94.7%), and 62% died without comorbidities as many as 72 people due to COVID-19. There is a significant relationship between clusters and comorbidities on the death of the elderly infected with COVID-19. Comorbidities (with comorbidities) are the most dominant influencing mortality in the elderly by 60.9% based on logistic regression model analysis involving four variables affecting the mortality of COVID-19 in the elderly,  and other factors influence the rest.